Stock Liquidity and Volatility in Investors’ Investment Decisions on the Indonesia Stock Exchange - Khatmi Tamtami Nisa; Mariani Salle Pasulu; Muhammad Nurwahyudi; Arifuddin Arifuddin; Darwis Said (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to understand the significance of stock liquidity and volatility in investment decision-making among Generation Z and Millennial investors on the Indonesia Stock Exchange. Research Method: This study employed a qualitative, phenomenological design. Data were collected through in-depth, semi-structured interviews with Generation Z and Millennial investors selected using purposive sampling. Data analysis was conducted using Miles' interactive model. Results and Discussion: The research findings indicate that stock liquidity is viewed as a form of investment security and flexibility. At the same time, volatility is perceived as both an opportunity and a risk. Investment experience shapes more rational decision-making, while social media and social circles serve as sources of investment education. Generation Z tends to focus on growth opportunities, whereas Millennials place greater emphasis on risk management. Implications: The research findings contribute to the development of financial literacy and to the design of investment education programs tailored to the characteristics of different investor generations. Originality: This study offers a phenomenological perspective on the interpretation of stock liquidity and volatility among Generation Z and Millennial investors in Indonesia.